2017
DOI: 10.3171/2016.5.jns152907
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of cilostazol against the development of shunt-dependent hydrocephalus after subarachnoid hemorrhage

Abstract: OBJECTIVE Chronic hydrocephalus develops in association with the induction of tenascin-C (TNC), a matricellular protein, after aneurysmal subarachnoid hemorrhage (SAH). The aim of this study was to examine if cilostazol, a selective inhibitor of phosphodiesterase Type III, suppresses the development of chronic hydrocephalus by inhibiting TNC induction in aneurysmal SAH patients. METHODS The authors retrospectively reviewed the factors influencing the development of chronic shunt-dependent hydrocephalus in 87 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…A local environment such as extracellular pH is reported to affect tenascin-C's function [1,38], and the functional relationships between tenascin-C and other matricellular proteins such as galectin-3 [1], periostin [39][40][41], and osteopontin [42,43] should be also investigated in EBI and delayed cerebral ischemia. An antiplatelet cilostazol inhibited post-SAH tenascin-C induction [44] and improved outcomes associated with reduced incidence of delayed cerebral infarction in a clinical setting [3].…”
mentioning
confidence: 99%
“…A local environment such as extracellular pH is reported to affect tenascin-C's function [1,38], and the functional relationships between tenascin-C and other matricellular proteins such as galectin-3 [1], periostin [39][40][41], and osteopontin [42,43] should be also investigated in EBI and delayed cerebral ischemia. An antiplatelet cilostazol inhibited post-SAH tenascin-C induction [44] and improved outcomes associated with reduced incidence of delayed cerebral infarction in a clinical setting [3].…”
mentioning
confidence: 99%
“…As reported by many authors, acute hydrocephalus is an independent factor directly related to SDHC. 8,28,39 Blood location, specifically in the third and fourth ventricles, plays a critical role in prognosis and SDHC development. 16,33,39 Therefore, mGraeb is a robust predictive model because it integrates several independent risk factors for SDHC in one scale: blood quantity, blood location, and acute hydrocephalus.…”
Section: Discussion Predicting Sdhc After Sahmentioning
confidence: 99%
“…A recent report by Nakatsuka et al suggested the use of cilostazol, an inhibitor of phosphodiesterase, as a preventive treatment for SDHC in SAH patients. 28 In a retrospective review of 87 patients they found that the incidence of SDHC was significantly lower in the groups receiving ci-lostazol (8.3%-12.8% vs 33.3%; p < 0.05). Microsurgical fenestration of the lamina terminalis has also been pointed out as a strategy to reduce SDHC incidence.…”
Section: Potential Preventive Therapies For Sdhcmentioning
confidence: 95%
“…The treatment target could be periostin itself, or the receptor integrins and the related molecules. In order to inhibit the post-aSAH induction of a representative of the periostin-related protein tenascin-C, cilostazol was used in a clinical setting of aSAH and promising efficacy was found [73,74]. In consideration of the diverse signal transduction associated with periostin, it is believed that periostin may be involved in multiple pathophysiologies other than the blood-brain barrier disruption in aSAH.…”
Section: Perspectivementioning
confidence: 99%